Etika Dan Tanggung Jawab Digital Bagi Siswa/I SMP Negeri 2 Sihotang Kabupaten Samosir - Mutiara S. Simanjuntak; Juanto Simangunsong; Aprima Matondang (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
SMP Negeri 2 Sihotang is located in Samosir Regency, which is one of the koban schools for flash floods that occur at the end of 2023. This PKM aims to increase awareness of ethics and digital responsibility among junior high school students. With the widespread use of digital technology, especially among teenagers, it is important to introduce the concept of ethics and responsibility in its use. This PKM will adopt an educative approach that involves students directly in the understanding of digital ethics and its impact on individuals and society. The method used with the Socialization method, as well as the creation of multimedia-based educational materials. The main target of this PKM is students of SMP Negeri 2 Sihotang in Samosir Regency. Through an approach that focuses on student participation, it is expected to create a better understanding of the importance of acting responsibly in a digital environment. The expected outcome of this PKM is an increase in students' awareness of ethical and responsible practices in the use of digital technology, as well as their ability to take wise decisions in online situations. Thus, this PKM is expected to make a positive contribution to the formation of good digital character and behavior among students of SMP Negeri 2 Sihotang and the wider community.